When Preferences for a Stable Interest Rate Become Self-Defeating - Ragna Alstadheim; Øistein Røisland (Norges Bank, 2016)
Monetary policy makers often seem to have preferences for a stable interest rate, in addition to stable inflation and output. In this paper we investigate the implications of having an interest rate level term in the loss function when the policymaker lacks commitment technology. We show that preferences for interest rate stability may lead to equilibrium indeterminacy. But even when determinacy is achieved, such preferences can become self-defeating, in the meaning of generating a less stable interest rate than in the case without preferences for interest rate stability. Aiming to stabilize the real interest rate instead of the nominal rate is more robust, as it always gives determinacy and also tends to give a more stable nominal interest rate than when the policymaker aims to stabilize the nominal rate.
hdl:11250/2495722
Keywords: E52; E58; 330; monetary policy; discretion; interest rate stability